2019
DOI: 10.1371/journal.pone.0219929
|View full text |Cite
|
Sign up to set email alerts
|

Cost-minimisation model of magnetic resonance-guided focussed ultrasound therapy compared to unilateral deep brain stimulation for essential tremor treatment in Japan

Abstract: Objective To investigate the cost differences between magnetic resonance-guided focussed ultrasound (MRgFUS) and unilateral deep brain stimulation (DBS) for the treatment of medication-refractory essential tremor (ET) in Japan using a cost-minimisation model. Methods A cost-minimisation model estimated total costs for MRgFUS and unilateral DBS by summing the pre-procedure, procedure, and post-procedure costs over a 12-month time horizon, using data from published source… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…This measure can be calculated from routine CT scans of the head. Compared to deep brain stimulation, focused ultrasound is less expensive [183,184].…”
Section: Focused Ultrasoundmentioning
confidence: 99%
“…This measure can be calculated from routine CT scans of the head. Compared to deep brain stimulation, focused ultrasound is less expensive [183,184].…”
Section: Focused Ultrasoundmentioning
confidence: 99%
“…A Japanese study looked at costs alone and also found MRgFUS to be cheaper than DBS. 45 However, these Japanese and American studies did not ascertain ICERs. 46,47 The ICERs and outcomes for the Canadian study were similar to this study.…”
Section: Discussionmentioning
confidence: 97%
“…The 2019 Japanese cost minimisation study (no quality of life estimate) was performed over 1 year. 47 MRgFUS was determined cost-saving (£2,892; converted 2018 JPY400,380); the total costs per procedure for MRgFUS £15,494 (converted 2018 JPY2,145,037) and unilateral DBS were £18,386 (converted from 2018 JPY2,545,417).…”
Section: Discussionmentioning
confidence: 99%